Toward the Discovery of Host-Defense Peptides in Plants - Petre, Benjamin (Frontiers in Immunology, 2020)
Defense peptides protect multicellular eukaryotes from infections. In biomedicine, a dominant conceptual framework refers to defense peptides as host-defense peptides (HDP), which are multifunctional peptides with both direct antimicrobial and immunomodulatory activities. No HDP has been reported in plants so far, and the very concept of HDP has not been captured yet by the plant science community. Plant science thus lacks the conceptual framework that would coordinate research efforts aimed at discovering HDPs in plants. In this perspective article, I used bibliometric and literature survey approaches to raise awareness about the HDP concept among plant scientists, and to encourage research efforts aimed at discovering plant HDPs. Such discovery would enrich our comprehension of the function and evolution of the plant immune system, and provide us with novel molecular tools to develop innovative strategies to control crop diseases.